2020
DOI: 10.1111/ijcp.13878
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of potentially inappropriate medications among Thai patients with heart failure

Abstract: Background Several medications may worsen heart failure (HF), and they are considered as potentially inappropriate medications for patients with heart failure (PIMHF). No studies reported the prevalence of PIMHF use and its associated factors in Thai HF patients. Objective To determine the prevalence of PIMHF use and identify factors associated with PIMHF use. Material and Method A cross‐sectional study was conducted using data on HF patients obtained from the electronic medical databases (EMDs) of two hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Most hospitalized older Buddhist monks had chronic diseases, and more than 50% had one or more chronic diseases. To a previous study, up to 90% of older people and 20% of Buddhist monks had various chronic diseases (Jenghua et al, 2019;National Office of Buddhism, 2017). This study found that hypertension was the most common chronic disease, consistent to a survey; up to 70% of the population had hypertension, which had a positive relationship with age (Yotsombut, 2010).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Most hospitalized older Buddhist monks had chronic diseases, and more than 50% had one or more chronic diseases. To a previous study, up to 90% of older people and 20% of Buddhist monks had various chronic diseases (Jenghua et al, 2019;National Office of Buddhism, 2017). This study found that hypertension was the most common chronic disease, consistent to a survey; up to 70% of the population had hypertension, which had a positive relationship with age (Yotsombut, 2010).…”
Section: Discussionmentioning
confidence: 83%
“…Based on the literature review, we found various studies on medication use behaviours and problems with medication used in adults, older adults and Buddhist monks. The problems could be summarized as multiple drug use, none adherence, the adjusted dose of medicine and side effects of medication use (Artsanthia & Techakuljareon, 2019; Champunot, 2011; Chotvirut & Tanchaloemchai, 2010; Darunthanom et al, 2019; Jenghua et al, 2019; Suvithanpatthanabandit et al, 2015; Suwannapong & Klungrit, 2019; Yotsombut, 2010). However, those studies were separately conducted and explored the problem of self‐medication in the community.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, irrational drug use is common in persons with chronic illnesses such as cancer (Seangrung et al, 2020 ) and diabetes mellitus (Yensabai et al, 2016 ). In addition, a high prevalence of potentially inappropriate medication use was found among older Thai persons (Jenghua et al, 2019 ; Vatcharavongvan & Puttawanchai, 2019 ).…”
mentioning
confidence: 99%